1986
DOI: 10.1172/jci112696
|View full text |Cite
|
Sign up to set email alerts
|

Heinz bodies induce clustering of band 3, glycophorin, and ankyrin in sickle cell erythrocytes.

Abstract: In earlier model studies we demonstrated that artificially denatured hemoglobin binds to and clusters the protein, band 3, in the plane of the erythrocyte membrane. To determine whether denatured hemoglobin also clusters band 3 in vivo, we have compared the locations of denatured hemoglobin aggregates (Heinz bodies) with band 3 in sickle cells using phase contrast and immunofluorescence microscopy. We report that where Heinz bodies are found associated with the cytoplasmic surface of the membrane, clusters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 38 publications
2
48
1
Order By: Relevance
“…In this case as pointed out by Waugh et a!. [11] no clustering of Band 3 can be expected. We used exactly the same experimental procedures for red cell separation and Heinz-body formation as were employed by Low et al [10].…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…In this case as pointed out by Waugh et a!. [11] no clustering of Band 3 can be expected. We used exactly the same experimental procedures for red cell separation and Heinz-body formation as were employed by Low et al [10].…”
mentioning
confidence: 51%
“…In another experiment we compared the intensity of the phenylhydrazine-induced fluorescence detected at the excitation range of rhodamine to that of the specific immunofluorescence of red cells in which an intracellular antigen spectrin was detected using rabbit antihuman spectrin and rhodamine-conjugated goat antirabbit IgG. While in recent experiments performed or~ haemoglobinopathic erythroeytes [11,12] the red cell autofluorescence was found to be negligible compared to the specific immunofluorescence, our experiment (where photography and printing of both samples were also carried out identically) showed that the intensity of phenylhydrazine-induced fluorescence is in fact comparable to that of the speci!ic immunofluorescence (data not sho,m,. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple physiologic events are thought to contribute to vaso-occlusion, including hemoglobin S polymerization with consequent RBC deformation [1], cell dehydration leading to increased hemoglobin polymerization [2,3], RBC adhesion to endothelial cells and extracellular matrix (ECM) proteins [4], and activation of coagulation [5][6][7]. Red blood cells containing predominantly hemoglobin S (SS RBC) adhere most avidly to laminin among ECM proteins [8].…”
Section: Introductionmentioning
confidence: 99%
“…A second postulate suggests that disulfide-linked hemoglobin adducts to critical membrane skeletal proteins, formed via hemoglobin thiyl radical attack of the protein free sulfhydryl groups, initiates red cell sequestration Jollow and McMillan, 1998). In support of this postulate, a number of investigators have shown that hemoglobin attachment to the cytosolic domain of band 3 causes alterations in the lateral distribution of this integral membrane protein leading to the binding of autologous antibodies on the external cell surface, which initiates erythrophagocytosis (Lutz et al, 1984;Waugh et al, 1986Waugh et al, , 1987Turrini et al, 1991).…”
Section: Discussionmentioning
confidence: 99%